2016
DOI: 10.3892/ijmm.2016.2789
|View full text |Cite
|
Sign up to set email alerts
|

Role of urotensin II in advanced glycation end product-induced extracellular matrix synthesis in rat proximal tubular epithelial cells

Abstract: Urotensin II (UII) was first recognized for its constrictive and natriuretic properties in fish almost 40 years ago, and recent studies have suggested that it exerts pro-fibrotic effects in a number of cell lines. In this study, we aimed to evaluate the role of UII in extracellular matrix (ECM) synthesis and secretion in advanced glycation end product (AGE)-stimulated rat proximal tubular epithelial cells (NRK-52E cells). UII promoted the proliferation of the NRK-52E cells in a dose-dependent manner over a con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
2
2
0
Order By: Relevance
“…Immunofluorescence staining of type IV collagen and fibronectin also indicated that UII stimulates their production by individual cells. These data are consistent with studies that reported an increase in fibronectin and collagen mRNA expression in rat proximal tubular epithelial cells and cardiac fibroblasts treated with UII 42 , 43 . Thus, a combination of increased proliferation and synthesis by individual GMCs may account for UII-induced ECM accumulation.…”
Section: Discussionsupporting
confidence: 92%
“…Immunofluorescence staining of type IV collagen and fibronectin also indicated that UII stimulates their production by individual cells. These data are consistent with studies that reported an increase in fibronectin and collagen mRNA expression in rat proximal tubular epithelial cells and cardiac fibroblasts treated with UII 42 , 43 . Thus, a combination of increased proliferation and synthesis by individual GMCs may account for UII-induced ECM accumulation.…”
Section: Discussionsupporting
confidence: 92%
“…To elucidate the mechanisms underlying the multiple protective effects of TMQ, we evaluated the levels of TGF-β1 and U-II using ELISA. Studies in the literature have shown that TGF-β1 and UT-II have many biological activities in processes such as proliferation, fibrosis, and inflammation [9,46]. As shown in Figure 1 of our study, TMQ treatment given after MPA-induced ON development significantly reduced fatty degeneration, osteonecrosis, 4-HNE, and 8-OHdG levels.…”
Section: Discussionsupporting
confidence: 66%
“…In the kidney, the expression of GPR14 is most abundant in distal convoluted tubules, collecting duct epithelial cells, and glomerular capillary endothelial cells [27]. Some studies have found that UII combined with GPR14 can exert biological effects such as vasoconstriction, cell proliferation, and extracellular matrix expression and secretion [28][29][30], regulate inflammatory signaling pathways such as JAK2/STAT3 by inducing the production of pro-fibrotic factors such as TGF-β1 [31], and involved in the occurrence and development of renal fibrosis [32]. These studies suggested that UII is the key factor leading to renal fibrosis.…”
Section: Discussionmentioning
confidence: 99%